Teaching Experience, Efficacy, and Performance among Kindergarten Teachers in Manicahan District: A Correlational Study - Asani, Salma Sabdahun (Utan Kayu Publishing, 2026)
Understanding how teaching experience and teacher efficacy relate to classroom performance is essential for strengthening early childhood education. This study examined the relationships among teaching experience, teacher efficacy, and teaching performance of kindergarten teachers in Manicahan District to determine whether professional experience and confidence translate into improved instructional performance. In this study, teaching experience is operationally defined as the teachers’ length of service in years in kindergarten teaching; however, when measured using a Likert-scale instrument, it refers to self-reported teaching practice engagement, which is interpreted as perceived teaching practice rather than actual years of service to avoid misleading conclusions. Teacher efficacy refers to teachers’ beliefs in their capability to perform instructional tasks effectively, while teaching performance refers to their actual performance ratings based on official evaluation records. Guided by the assumption that greater experience enhances efficacy and performance, the study employed a descriptive–correlational research design. Data were collected from 35 kindergarten teachers during the 2024–2025 academic year using a validated survey questionnaire and official performance records. Statistical analyses included descriptive statistics, Pearson product–moment correlation, and analysis of variance. Results indicated that teachers demonstrated high levels of teaching experience and teacher efficacy and were rated very satisfactory in performance. ** Teaching experience showed a significant positive relationship with teacher efficacy (r = .439, p = .009, 95% CI [, ], moderate effect) but was not significantly related to teaching performance (r = –.096, p = .584, small effect). Teacher efficacy also did not significantly correlate with teaching performance (r = .057, p = .751, small effect). These findings indicate that while experience is associated with higher efficacy, neither experience nor efficacy alone directly translates into improved teaching performance, suggesting the need for further investigation of other influencing factors. The study highlights the importance of strengthening professional development systems, instructional support, and school-based mentoring to enhance early childhood teaching effectiveness.